1981
DOI: 10.1002/ar.1092010408
|View full text |Cite
|
Sign up to set email alerts
|

Ephemeral, rudimentary glomerular structures in the mesonephros of the mouse

Abstract: The fine morphology of glomeruli present in the mesonephroi of mouse embryos from days 12 to 14 of gestational age is described. The glomeruli are rudimentary, ephemeral structures which probably result from temporary juxtaposition of a blood capillary to the ventral extremity of a mesonephrictubule. Yet, they might possess a certain degree of functionality.While the studies of Leeson (1960) in the rabbit, Davies and Davies (1950) and Zamboni et al. (1981) in the sheep, and De Martino and Zamboni (1966) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
2
Order By: Relevance
“…Some mesonephric nephron-like structures had a rudimentary glomerulus in contrast to previous studies of human ES cells that reported the presence of nephron-like structures with discernible glomeruli and tubules in ES cell-derived teratomas (1,43). This discrepancy seems to depend principally on species differences, i.e., the human fetus has a well-developed mesonephros with distinct glomeruli (27), whereas the mouse fetus does not (48). In fact, no discernible vascularized glomeruli were observed in the mesonephros of mouse embryos used as controls.…”
Section: Discussioncontrasting
confidence: 83%
“…Some mesonephric nephron-like structures had a rudimentary glomerulus in contrast to previous studies of human ES cells that reported the presence of nephron-like structures with discernible glomeruli and tubules in ES cell-derived teratomas (1,43). This discrepancy seems to depend principally on species differences, i.e., the human fetus has a well-developed mesonephros with distinct glomeruli (27), whereas the mouse fetus does not (48). In fact, no discernible vascularized glomeruli were observed in the mesonephros of mouse embryos used as controls.…”
Section: Discussioncontrasting
confidence: 83%
“…These authors were unable to detect a placental defect and concluded that polyhydramnios, which precedes cyst formation, is caused by abnormal proximal tubular function and excessive loss of renal solutes. Our data, however, are not consistent with this conclusion since we see polyhydramnios as early as E11.5, prior to filtration by the metanephric kidney [40]. In addition, Pkd endo− embryos lack a demonstrable renal phenotype yet they have significant polyhydramnios, making it unlikely that this is renal in origin.…”
Section: Discussioncontrasting
confidence: 82%
“…Obvious differences exist between the mesonephroi of primates which display a "conventional" type of organization, are relatively long-lived, function as excretory organs, and are still undergoing differentiation when the gonad begins to develop, and: 1) those of ruminants which not only are prominently developed but also peculiarly organized due to the presence of a giant nephron (Bremer, 1915;Davies and Davies, 1950;Shumkina, 1960;Tiedemann, 1976;Zamboni and Upadhyay, 19821, are highly functional, and are already involuting prior to onset of gonadal development; and 2) those of rodents which are ephemeral, incomplete, non-functional and still in very early formative stages at the time the PGCs arrive in the genital ridge (Bremer, 1916;Brambell, 1927b;Brown, 1931;Torrey, 1943;Vetter and Gibley, 1966;Zamboni and Upadhyay, 1981). Since in primates the mesonephros does not seem to play a critical role in the early assembly of the gonad in sharp contrast to ruminants and rodents where its role as source of the somatic-cell population of the gonadal blastema has been convincingly demonstrated one may speculate in the possibility that the differences in patterns and mechanisms of gonadal development may be attributable to the differences that exist among species with regard to the structural complexity, functionality, and stages of differentiatiodinvolution of their mesonephroi on the one hand, and the time of gonadal development on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has contributed to the current understanding of the role of the mesonephros in gonadal development with studies in the mouse (Merchant and Zamboni, 1972;Upadhyay et al, 1979Upadhyay et al, , 1981 and the sheep Zamboni and Upadhyay, 1982), animals that are at the opposite extremes with regard to degrees of mesonephric development, structural complexity, and functionality. The mesonephroi of the mouse, like those of the rat (Torrey, 1943), are incompletely developed, rudimentary, and non-functional (Bremer, 1916;Brambell, 1927b;Brown, 1931;Vetter and Gibley, 1966;Zamboni and Upadhyay, 1981); in contrast, those of the sheep and other ruminants are of voluminous dimensions, possess a peculiar organization of considerable complexity, and are fully functional as filtering and excretory organs (Bremer, 1915;Davies and Davies, 1950;Shumkina, 1960;Tiedemann, 1976;Zamboni and Upadhyay, 1982). As a logical evolution of those studies, we decided to focus on gonadal development in the primates not only because of the obvious biomedical relevance of these animals, but also because they are characterized by degrees of mesonephric structural development and complexity which are intermediate between the rodent and ruminant extremes cited above (Torrey, 1954;Davies, 1963;De Martino and Zamboni, 1966;Patten, 1968;Du Bois, 1969;Cotrutz et al, 1971;Hamilton and Mossman, 1972;Koga, 1972;Arey, 1974;Torrey and Feduccia, 1979).…”
Section: Introductionmentioning
confidence: 99%